Relationship between Learning Motivation and Students' Learning Achievements in English Education Study Program at Nahdlatul Ulama University of Blitar - Aisyah, Zenita Sholihatul; Makrifah, Istina Atul; Saifudin, Ahmad; Mubarok, Tyas Alhim (BRILIANT: Jurnal Riset dan Konseptual, 2023)
The purpose of this research is to ascertain the relationship between learning motivation and academic achievement in second semester students of the English Education Study Program at Nahdlatul Ulama University of Blitar.  The design of this research is correlational quantitative. Interviews, documentation, and questionnaires were used to gather the data. The results of the validity analysis showed that as many as 25 questions were declared valid without exception, while the degree of validity ranged from 0.404 to 0.771.  The reliability results show a coefficient of 0.915 and it is declared reliable.  Chi-Square test and an analogous Fisher Exact test are used in data analysis. Of the 31 respondents, there were 17 students with high motivation (54.8%) and 14 students (45.2%) with low motivation.  Students with cum laude GPA as many as 24 respondents (77.4%) and very satisfactory GPA as many as 7 students (22.6%).  The outcome of the statistical test has a p-value of 1,000 (p > 0.05). This indicates that there is no relationship between learning motivation and academic achievement among second semester English Education Study Program students at Nahdlatul Ulama University of Blitar.